2020
DOI: 10.1167/iovs.61.10.19
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of Structural and Functional Changes in Presence of Reticular Pseudodrusen Associated With Age-Related Macular Degeneration

Abstract: To examine longitudinal changes of retinal thickness and retinal sensitivity in patients with intermediate age-related macular degeneration (iAMD) and predominantly reticular pseudodrusen (RPD). METHODS. At baseline 30 eyes of 25 iAMD patients underwent optical coherence tomography imaging, mesopic and scotopic fundus-controlled perimetry (FCP) with follow-up examinations at month 12 (20 eyes), 24 (12 eyes), and 36 (11 eyes). Thicknesses of different retinal layers and results of FCP testing (n = 56 stimuli) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 46 publications
3
26
0
Order By: Relevance
“…Although researchers in macular disease were amongst the first to recognise the benefits of MP, initially due to its compensation for poor fixation in GA [138], more recently its potential as an endpoint has moved centre stage [6, 12, 13]. Interest in mesopic and scotopic MP modalities has increased as their ability to capture subtle functional deficits in early and intermediate AMD [51, 59, 139-142] and quantify progression over time [143, 144] has been demonstrated. Of note, significant reductions in mesopic sensitivity over a period as short as 12 months have been shown [73, 145], implying MP endpoints may allow for shorter trial durations.…”
Section: Macular Degenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although researchers in macular disease were amongst the first to recognise the benefits of MP, initially due to its compensation for poor fixation in GA [138], more recently its potential as an endpoint has moved centre stage [6, 12, 13]. Interest in mesopic and scotopic MP modalities has increased as their ability to capture subtle functional deficits in early and intermediate AMD [51, 59, 139-142] and quantify progression over time [143, 144] has been demonstrated. Of note, significant reductions in mesopic sensitivity over a period as short as 12 months have been shown [73, 145], implying MP endpoints may allow for shorter trial durations.…”
Section: Macular Degenerationmentioning
confidence: 99%
“…With respect to future alternative endpoints, reporting change in PWS is also likely to be important. PWS offers a more robust way of identifying local alterations and, in combination with multimodal imaging, has enhanced our understanding of specific functional deficits present with precise structural changes in AMD [55, 143, 144]. In fact, PWS over reticular pseudodrusen has been shown to exhibit faster progression than that detected in unremarkable retinal regions in the same eye.…”
Section: Macular Degenerationmentioning
confidence: 99%
“…RPD lesions visible in fundus images of AMD patients confer increased risk of advanced disease. 24 , 51 53 …”
Section: Diseases Presenting With Reticular Fundus Patternsmentioning
confidence: 99%
“…With the availability of OCT angiography (OCTA), several groups demonstrated decreased flow signals at the CC level and increased areas of flow deficits in eyes with RPD 9 , 10 . Using OCT, mesopic and scotopic fundus-controlled perimetry, Sassmannshausen et al demonstrated progressive outer retinal degeneration and corresponding impairment of photoreceptor function in eyes with RPD over 3 years 11 . Zhang et al used adaptive optics scanning laser ophthalmoscopy over a 3.5-year period to describe the evolution of progression and regression of individual RPD lesions presumably reflecting the process of outer retinal atrophy 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%